Women's religious activity in the Roman Republic - Schultz, Celia E. (Studies in the history of Greece and Rome., 2006)
Schultz demonstrates that in addition to observances of marriage, fertility, and childbirth, there were more--and more important--religious opportunities available to Roman women than are commonly considered. Her study of ancient literature, inscriptions, and archaeological remains from the fifth to the first century B.C.E. shows that women honored gods unaffiliated with domestic matters, including Hercules and Jupiter; they took part in commercial, military, and political rites; they often worshipped alongside men; and they were not confined to the private sphere, the traditional domain of wo.